2015
DOI: 10.1016/j.pjnns.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and cortisol profiles in patients with pituitary tumors

Abstract: The optic tract section at the optic chiasm is expected to disturb the suprachiasmatic nucleus (SCN) rhythm, circadian rhythm and melatonin secretion rhythms in humans, although detailed studies have never been conducted. The aim of this paper was to describe melatonin and cortisol profiles in patients with a pituitary tumor exerting optic chiasm compression. Six patients with pituitary tumors of different size, four of whom had significant optic chiasm compression, were examined. In each brain, MRI, an ophtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Decreased levels of melatonin, resulting in disturbed circadian rhythm, may also be caused by optic chiasm exertion. It may occur in pituitary macroadenoma -in a reported case series one of four patients with macroadenoma pressing the optic chiasm, and one patient with macroadenoma but without pressure had a flattened rhythm of melatonin secretion [20] . In another observational study, abnormalities in melatonin secretion were reported in 70,59% of patients with non-functioning pituitary macroadenomas [21] .…”
Section: Discussionmentioning
confidence: 96%
“…Decreased levels of melatonin, resulting in disturbed circadian rhythm, may also be caused by optic chiasm exertion. It may occur in pituitary macroadenoma -in a reported case series one of four patients with macroadenoma pressing the optic chiasm, and one patient with macroadenoma but without pressure had a flattened rhythm of melatonin secretion [20] . In another observational study, abnormalities in melatonin secretion were reported in 70,59% of patients with non-functioning pituitary macroadenomas [21] .…”
Section: Discussionmentioning
confidence: 96%
“…These findings suggested involvement of circadian clock in pituitary tumorigenesis. In support of this, patients with pituitary adenomas are associated with severe disturbances in circadian rhythms, as exemplified by disrupted sleep-wake cycle, altered diurnal patterns of melatonin and cortisol, and disturbed movement rhythm [22,[24][25][26].…”
Section: Disruption Of Pituitary Clock Genes In Patients With Pituita...mentioning
confidence: 99%
“…These irregular sleep-wake patterns may be attributable to disruption in normal diurnal melatonin secretion. Altered patterns of melatonin secretion with shifted or absent nocturnal peak and/or inadequate daytime suppression have been demonstrated in some patients with tumors of the sellar/parasellar, suprasellar/hypothalamic, and pineal regions [46][47][48][49][50][51][52]. The specific melatoninregulating circadian pathway affected varies with tumor location.…”
Section: Circadian Rhythm Sleep Disordersmentioning
confidence: 99%
“…The specific melatoninregulating circadian pathway affected varies with tumor location. Tumors affecting the optic chiasm may interrupt photoneural input to the SCN travelling via the retinohypothalamic tract [51]. Sellar and suprasellar tumors may directly damage the SCN or its melatonin-regulating afferents [47,50].…”
Section: Circadian Rhythm Sleep Disordersmentioning
confidence: 99%